Microstructural effects on the electrical properties of grain boundary Fe-doped LSGM - Gomes, Eduarda (2008)
Mixed conductors based on grain boundary Fe-doped La0.95Sr0.05Ga0.90Mg0.10O3 − δ (LSGM) ceramics were obtained by selectively doping the grain boundaries with Fe. This was achieved using LaFeO3 − δ layers screen-printed onto LSGM, after annealing at high temperature in air for several hours to promote Fe diffusion into LSGM. The influence of the number of impregnation cycles, temperature of impregnation and microstructure of the host LSGM was evaluated by impedance spectroscopy and oxygen permeability. The impedance spectra consist of high and low frequency semicircles, ascribed to bulk and grain boundaries. The amplitude of both contributions decreases with increasing impregnation temperature and time, suggesting the onset of electronic conduction along grain boundaries. The effect is stronger for ceramics with larger grain size. The observed trends are fully consistent with estimates of p-type electronic conductivity obtained from oxygen permeability measurements using a simplified electrochemical cell.